Thermal and friction drop characteristic of heat exchangers with elliptical tubes and smooth fins//Caracterización térmica e hidráulica de intercambiadores de calor con tubos elípticos y aletas lisas - Borrajo-Pérez, Rubén; Ititzo-Yanagihara, Jurandir; González-Bayón, Juan José (Ingeniería Mecánica. Revista electrónica. ISSN 1815-5944, 2012)
Pressure drop and heat transfer are the most important parameters in compact heat exchanger. There is a lack of information in the literature about heat exchanger with elliptical tube. The objective of this work was the experimental characterization of compact heat exchangers models using elliptical tube with eccentricity of 0,5 and smooth fins. The Reynolds numbers and the spacing were varied and always inside laminar regime. The experiments were conducted in an open wind tunnel using sublimation of naphthalene and the heat and mass transfer analogy. As results, the average and local Nusselt number and friction factor for 36 models were obtained. Correlations for Colburn and friction factors were presented. This correlations were obtained for 200<Re<1500 and isothermal fins. These are the first correlations presented in the open literature covering a wider range of pitches. A baseline for future implementations of enhancement heat transfer techniques is presented. Key words: friction factor, heat transfer coefficient, elliptical tube, compact heat exchanger. _______________________________________________________________________________ Resumen: Caída de presión y transferencia de calor son importantes parámetros en intercambiadores de calor. Existe falta de información cuando de intercambiadores de calor y tubos elípticos se trata. El objetivo del trabajo fue caracterizar experimentalmente modelos de intercambiadores de calor con tubos elípticos y aletas lisas. El numero de Reynolds y los espaciamientos fueron variados, dentro del régimen laminar. Los experimentos fueron desarrollados en un túnel de viento de circuito abierto usando la sublimación de naftaleno y la analogía calor y masa. Los números de Nusselt medio, locales y el factor de fricción fueron obtenidos en forma de correlaciones de Factores de Fricción y Colburn. Las correlaciones, validas para 200<Re<1500 y aleta isotérmica. Son las primeras correlaciones que se aplican a un tan amplio rango de espaciamientos. Se presenta una línea base para futura comparación en la implementación de técnicas de intensificación de transferencia. Palabras claves: factor de fricción, coeficiente de transferencia de calor, tubos elípticos, intercambiadores de calor compactos.